Teacher leadership for education for sustainable development in indonesian vocational schools: Evidence from students' perspectives - Tutik Susilowati; Yosep Tegar Prameswara (Jurnal Pendidikan Vokasi, 2026)
This study investigates how teacher leadership supports Education for Sustainable Development (ESD) in Indonesian vocational high schools from students’ perspectives. Specifically, it examines the effects of instructional, servant, and transformational leadership on students’ perceptions of sustainability-oriented learning practices. Unlike previous studies, which have primarily focused on principal leadership or individual leadership approaches, this study integrates instructional, transformational, and servant leadership into a unified model to explain ESD implementation from students’ perspectives. Using a quantitative cross-sectional design, data were collected through an online questionnaire completed by 779 vocational high school students in Central Java and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that instructional leadership (β = 0.404), transformational leadership (β = 0.243), and servant leadership (β = 0.157) each have significant positive effects on sustainability-oriented education, collectively explaining 52.9% of the variance. Instructional leadership emerged as the strongest predictor, suggesting that lesson design, the facilitation of critical thinking, constructive feedback, and effective classroom practices are central to embedding ESD values in vocational education. The findings imply that professional development programs for vocational teachers should integrate pedagogical, inspirational, and ethical leadership competencies to strengthen ESD implementation. The study is limited by its cross-sectional design, reliance on student self-reports, convenience sampling, and regional focus. Therefore, future research should employ longitudinal, qualitative, and multi-stakeholder approaches to provide stronger evidence regarding causal relationships and contextual factors influencing ESD implementation.